Plagiarism in Secondary School: Minor Inaction with Major Consequences - Yury V. Chekhovich; Olga S. Belenkaya (National Research Mordova State University, 2023)
Introduction. The ease of searching and copying someone elseʼs text on almost any topic is one of the most important reasons for the prevalence of plagiarism in academic papers. While plagiarism detectors have become a common tool for universities, such systems are practically not used in secondary schools. It is considered to be a serious problem, that high school graduates are unprepared for the academic papers' originality requirements. Universities are making efforts to overcome this lack of readiness. The authors study the attitude of teachers and learners of the Russian secondary schools toward the problem of plagiarism. Materials and Methods. An anonymous online survey of teachers (n = 2,286) and learners (m = 4,555) of secondary schools in the Vologda, Kaliningrad and Lipetsk regions of the Russian Federation was conducted. The survey was carried out through the Google Forms service. The quantitative and qualitative analysis of the obtained data was carried out. Results. Learners acquire the habit of plagiarism already in secondary school. Secondary school learners are loyal to copying someone elseʼs text without reference to the source; although they partially admit that by doing so they do wrong. Teachers are less tolerant to this and ready to respond to plagiarism in learners' papers by lowering marks/grades or by requiring learners to redo the work. Teachers do not always clearly understand which borrowings can be considered legitimate and correct, and which ones are not, they cannot explain this to their learners, cannot instill in them the necessary academic integrity, and cannot establish clear criteria for works evaluation.The use of plagiarism detection systems in schools is unsystematic and it is often the result of the initiative of individual teachers. There is also no methodology for using plagiarism detection systems in secondary schools. Discussion and Conclusion. The conducted studies for the first time provided actual confirmation of the hypotheses. It means that it is necessary to include plagiarism detection systems in the toolkit used in secondary school. We have obtained evidence, that it is necessary to implement such tools in the secondary education system step by step, as well as to create conditions, so that school teachers can acquire relevant skills. The materials of the article will be useful to scientists who study the problems of secondary and high education, managers of the secondary education system at all levels, teachers, lecturers and learners of pedagogical universities.